A case-control study on family environment characteristics of accident-prone children. Issue 4 (1st December 2014) - Chen, Sisi; Zhou, Leshan
Abstract : Objective: The purpose of the current study was to determine the family environment characteristics of accident-prone children, and the influencing factors to provide a reference for accident prevention and intervention for these children. Methods: One hundred forty-seven cases of accident-prone children were screened out from a cross-sectional survey as the case group, and another 147 cases of non-accidentally-injured children served as the control group. The Chinese version of the Family Environment Scale (FES-CV) was applied to evaluate the family environment characteristics of subjects from both groups. Results: The incidence of accident-prone children was 9.42%. Comparing the scores of all factors in the FES-CV, the contradiction score of the case group was higher than the control group, while the scores of other factors was lower than the control group. Differences between the two groups with respect to intimacy, emotional expression, contradiction, independence, and success scores were statistically significant, but differences in informative and entertaining scores were not. Differences with respect to family type, financial status, education, guardian, age of guardian, marital status, and health status were statistically significant. As revealed by regression analysis, intimacy (OR=0.530), emotional expression (OR=0.749), and independence (OR=0.732) were protective factors for accident proneness, while rigorous education (OR=2.101) and indulgence or indifference/violence (OR=7.629) were risk factors for accident proneness. Conclusion: Family environment influence child accident proneness, thus preventive interventions should be provided according to the characteristics of the family environment.